2008
DOI: 10.1111/j.1742-1241.2008.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole monotherapy in patients with rapid-cycling bipolar I disorder: an analysis from a long-term, double-blind, placebo-controlled study

Abstract: Aims Rapid-cycling bipolar disorder is difficult to treat and associated with greater morbidity than non-rapid-cycling disease. This post hoc analysis evaluated 28 patients with rapid-cycling bipolar I disorder from a 100-week, double-blind, placebo-controlled study assessing long-term efficacy, safety and tolerability of aripiprazole in patients with bipolar I disorder (most recently manic/mixed). Methods Following ≥ 6 consecutive weeks’ stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…In these studies, the total relapse rates were significantly lower in the aripiprazole group than in the placebo group in the study by Keck et al (2007) (33% in the aripiprazole group and 52% in the placebo group) (Keck et al, 2007), and in the study by Muzina et al the time to relapse was significantly longer in the aripiprazole group than in the placebo group at week 100 (hazard ratio = 0.18, log-rank p = 0.017) (Muzina et al, 2008). …”
Section: 25mentioning
confidence: 93%
See 4 more Smart Citations
“…In these studies, the total relapse rates were significantly lower in the aripiprazole group than in the placebo group in the study by Keck et al (2007) (33% in the aripiprazole group and 52% in the placebo group) (Keck et al, 2007), and in the study by Muzina et al the time to relapse was significantly longer in the aripiprazole group than in the placebo group at week 100 (hazard ratio = 0.18, log-rank p = 0.017) (Muzina et al, 2008). …”
Section: 25mentioning
confidence: 93%
“…Few studies (Fountoulakis et al, 2011) (Keck et al, 2009;Muzina et al, 2008) showed promising efficacy of aripiprazole. Therefore, it may be more appropriate to use relapse rates as the primary outcome in the maintenance phase than in the acute phase in clinical practice, because the maintenance phase has a longer period of follow-up than the acute phase.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations